Pengaplikasian Model Regresi Linier Berganda Multivariat terhadap Data Cabang Olahraga Angkat Berat - Azmy Rabah; Suwanda (Bandung Conference Series: Statistics, 2023)
Abstract. Regression analysis is one analysis that is widely used. Regression analysis is used to perform predictions and forecasts. Regression analysis can also be used to understand which independent variables can be related to the dependent variable, as well as to determine the form of the relationship. Multiple linear regression is a regression model that involves more than one independent variable and a dependent variable (response). For this reason, it is necessary to test the meaning of regression simultaneously. In addition, the determination of the confidence interval of response prediction must involve correlation among the dependent variables. In this thesis, the implementation of multivariate regression on weightlifting sports data will be discussed, namely squat or Squat weight modeling (Y 1), bench weight pressed or Bench (Y 2), weight lifted or Deadlift (Y3), over Age (Z1) and Body weight (Z2). From the model obtained, it can be useful to make confidence intervals from the response values of Squat (Y1), Bench (Y 2), Deadlift (Y3) based on certain age (Z1) and Body weight (Z2) values outside the analyzed sample. Because the data used are world championship results, the qualification standards above apply to world-level weightlifting events. For national level events, the standard can be lowered and for the provincial level, the standard can be lowered again lower than the national level. There is a linear relationship between the type of squat weight lift or Squat (Y 1), bench weight pressed or Bench (Y 2), weight lifted or Deadlift (Y3), over Age (Z1) and Body weight (Z2) which is significant at a real level of 5%. The effect of the Age (Z 1) variable on the type of Squat (Y1), Bench (Y 2), and Deadlift (Y2) is negative. The effect of variable Body Weight (Z 2) on the type of Squat (Y1), Bench (Y2), and Deadlift (Y3) is positive. From a 50% confidence interval, a response prediction value is obtained that can be used as a minimum standard to qualify for participation in weightlifting competitions. Abstrak. Analisis regresi adalah salah satu analisis yang luas pemakaiannya. Analisis regresi digunakan untuk melakukan prediksi dan ramalan. Analisis regresi juga dapat digunakan untuk memahami variabel – variabel bebas mana saja yang dapat berhubungan dengan variabel terikat, serta untuk mengetahui bentuk hubungan tersebut. Regresi linear berganda merupakan model regresi yang melibatkan lebih dari satu variabel independent dan sebuah variabel dependen (Respon). Untuk itu perlu dilakukan pengujian keberartian regresi secara simultan. Selain itu, penentuan selang kepercayaan prediksi respon harus melibatkan korelasi diantara variabel dependen. Dalam skripsi ini akan dibahas implementasi regresi multivariat pada data olah raga angkat berat yaitu pemodelan berat badan jongkok atau Squat (Y1), berat bangku yang ditekan atau Bench (Y2), beban yang diangkat atau Deadlift (Y3), atas Usia(Z1) dan Berat badan (Z2). Dari model yang diperoleh dapat bermafaat untuk membuat selang kepercayaan dari nilai respon Squat (Y1), Bench (Y2), Deadlift (Y3) berdasarkan nilai usia (Z1) dan Berat badan (Z2) tertentu di luar sampel yang dianalisis. Karena data yang digunakan adalah hasil kejuaraan dunia, maka standar kualifikasi diatas berlaku untuk pertandingan angkat berat tingkat dunia. Untuk event tingkat nasional dapat diturunkan standarnya dan untuk tingkat Provinsi dapat diturunkan lagi standarnya lebih rendah dari tingkat Nasional. Terdapat hubungan linier antara jenis angkatan berat badan jongkok atau Squat (Y1), berat bangku yang ditekan atau Bench (Y2), beban yang diangkat atau Deadlift (Y3), atas Usia(Z1) dan Berat badan (Z2) yang signifikan pada taraf nyata 5%. Pengaruh variable Usia (Z1) pada jenis angkatan Squat (Y1), Bench (Y2), dan Deadlift (Y2) yang bersifat negative. Pengaruh variable Berat Badan (Z2) pada jenis angkatan Squat (Y1), Bench (Y2), dan Deadlift (Y3) yang bersifat positif. Dari selang kepercayaan 50% diperoleh nilai prediksi respon yang dapat dijadikan standar minimal untuk dapat lolos pada keikutsertaan kompetisi angkat berat.